A Solid‐State Fibriform Supercapacitor Boosted by Host–Guest Hybridization between the Carbon Nanotube Scaffold and MXene Nanosheets. Issue 29 (25th June 2018) - Yu, Chenyang; Gong, Yujiao; Chen, Ruyi; Zhang, Mingyi; Zhou, Jinyuan; An, Jianing; Lv, Fan; Guo, Shaojun; Sun, Gengzhi
Abstract: Fiber‐shaped supercapacitors with improved specific capacitance and high rate capability are a promising candidate as power supply for smart textiles. However, the synergistic interaction between conductive filaments and active nanomaterials remains a crucial challenge, especially when hydrothermal or electrochemical deposition is used to produce a core (fiber)–shell (active materials) fibrous structure. On the other hand, although 2D pseudocapacitive materials, e.g., Ti3 C2 T x (MXene), have demonstrated high volumetric capacitance, high electrical conductivity, and hydrophilic characteristics, MXene‐based electrodes normally suffer from poor rate capability owing to the sheet restacking especially when the loading level is high and solid‐state gel is used as electrolyte. Herein, by hosting MXene nanosheets (Ti3 C2 T x ) in the corridor of a scrolled carbon nanotube (CNT) scaffold, a MXene/CNT fiber with helical structure is successfully fabricated. These features offer open spaces for rapid ion diffusion and guarantee fast electron transport. The solid‐state supercapacitor based on such hybrid fibers with gel electrolyte coating exhibits a volumetric capacitance of 22.7 F cm −3 at 0.1 A cm −3 with capacitance retention of 84% at current density of 1.0 A cm −3 (19.1 F cm −3 ), improved volumetric energy density of 2.55 mWh cm −3 at the power density of 45.9 mW cm −3, and excellent mechanical robustness. Abstract : A host–guest hybrid fiber with helical structure is successfully fabricated by incorporating MXene nanosheets (Ti3 C2 T x ) in the corridor of a scrolled carbon nanotube scaffold. A solid‐state supercapacitor based on such hybrid fibers with gel electrolyte coating exhibits improved volumetric capacitance with superior rate capability, improved volumetric energy density, and excellent mechanical robustness.